(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
Background: Elaborate Cardiotocography (CTG) is the most commonly used test for antepartum and intrapartum fetal surveillance because it gives information via the cerebro-cardiac response of fetal cerebral activity, which is modified by the hypoxia. Objective: This study was designed to compare the perinatal outcomes among the normal and abnormal CTG groups. Method: It was a prospective observational study carried out in the Department of obstetrics, BSMMU during the period July 2006 to July 2008. Hundred consecutive normal and hundred consecutive abnormal CTC tracings were collected from patients who were advised to perform CTG after admission. Both labour and non-labour patients were included. Interpretation of CTG was done based on FlGO recommendation (1987). Pregnancy and neonatal data were obtained and the findings were correlated with the FHR tracing. Statistical analysis was carried out by student’s unpaired t-test, X2 and Z-test. Level of significance was set at P value < 0.05. Results: Out of 100 abnormal CTG, 30% had tachycardia, 42% had deceleration, 38% was non reactive, 4% had absence beat-to-beat variability and 4% had fetal bradycardia. There was significantly higher caesarean delivery, lower apgar score, higher requirement of neonatal resuscitation and admission at neonatal unit and higher perinatal death among the abnormal CTG group. The abnormal fetal outcome was found highest in heart rate deceleration group. Conclusion: CTG can be continued as a good screening test of fetal surveillance but it is not the sole criteria to influence the management of high-risk pregnancies. Abnormal CTG should be supplemented with other test before intervention. Key words: CTG; Perinatal outcome. DOI: 10.3329/bsmmuj.v2i1.3706 BSMMU J 2009; 2(1): 18-24